UTILIZATION OF GEOGRAPHIC INFORMATION SYSTEM BASED ON UNMANNED AERIAL VEHICLE (UAV) FOR DETAILED MAPPING OF SRIWEDARI CULTURAL HERITAGE COMPLEX IN SURAKARTA CITY - Sari, Dewi Novita; Utomo, Tri Cahyo; Doriski, Muhammad (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2024)
Sriwedari cultural heritage complex in the City of Surakarta, Middle Java, is one of the buildings from the golden era of Keraton Kesunanan of Surakarta. Sriwedari park was built as a recreation area, entertainment, and recreation place for the Keraton family, which is why it’s called “Kebon Rojo” (Park of King). Besides being a park, there are a couple of other cultural heritage buildings like Radya Pustaka museum, Wayang Orang Building, Sriwedari Stadium, and Segaran. According to the Ministry of Education and Culture Republic of Indonesia, Sriwedari has become a kind of cultural heritage in the form of sites. The purpose of this research (1) Utilization of spatial based technology using a Geographic Information System that can map in detail the location of cultural heritage with the data sources from the Unmanned Aerial Vehicle (UAV) complete with the coordinate position and supporting information; (2) 3D Visualization using GIS-based software for distributive functional communication media that is communicative for the people. There are three stages of methods in this research. First, license/permission and collecting coordinate data (Ground Control Point) GCP, data of object distance in the field, and other information related to functions of every building. Second, UAV data processing uses spatial-based software, Agisoft Photoscan, and ArcGIS. Third, 3D and 2D map visualization about the building detail, function, and other information is available at Sriwedari Cultural Heritage Complex.